Geoscience model service integrated workflow for rainstorm waterlogging analysis. Issue 7 (3rd July 2021) - Tan, Xicheng; Jiao, Jingguo; Chen, Nengcheng; Huang, Fang; Di, Liping; Wang, Jinchuan; Sha, Zongyao; Liu, Jin
ABSTRACT: This paper proposed a geoscience model service integrated workflow-based rainstorm waterlogging analysis method to overcome the defects of conventional waterlogging analysis systems. In this research, we studied a general OGC WPS service invoking strategy, an automatic asynchronous invoking mechanism of WPS services in the BPEL workflow, and a distributed waterlogging analysis services integrated workflow to realize the reconstruction of a waterlogging analysis model based on the proposed method. The proposed method can make use of the flexible adjustment capability of the workflow and not only overcomes the inherent defects of conventional geoscience analysis methods but also realizes the integration and calculation of distributed geospatial data, models and computing resources automatically. The method has better construction convenience, execution reliability, extensibility and intelligence potential than a conventional method and has important value for dealing with more natural disasters and environmental challenges.